An economic analysis of prophylactic lymphovenous anastomosis among breast cancer patients receiving mastectomy with axillary lymph node dissection. Issue 8 (23rd March 2020) - Squitieri, Lee; Rasmussen, Petra W.; Patel, Ketan M.
Abstract: Background and Objectives: Prophylactic lymphovenous anastomosis (LVA) has been shown to decrease the incidence of postoperative lymphedema among patients receiving mastectomy with axillary lymph node dissection (ALND). However, the economic impact of this intervention on overall healthcare costs has not been adequately studied and insurance reimbursement for lymphedema treatment is limited resulting in substantial out‐of‐pocket patient expenses. Methods: We performed a cost‐minimization decision analysis from the societal perspective to assess two different patient scenarios: (a) mastectomy with ALND alone, (b) mastectomy with ALND and prophylactic LVA. Results: The annual cost of lymphedema‐related care is estimated to be 5, 691.88 (3, 160.52 direct, 2, 531.36 indirect). If all patients undergoing mastectomy with ALND undergo prophylactic LVA, the average expected lifetime cost per patient in the entire population (whether or not they develop lymphedema) is approximately 6, 295.61, compared to 13, 942.26 if no patients in the same population receive prophylactic LVA. Conclusions: Prophylactic LVA is economically preferred over mastectomy and ALND alone from a cost minimization perspective, and results in an average of 7, 646.65 (45.2%) cost saving per patient over the course of their lifetime.